1998
DOI: 10.1016/s0045-7949(97)00061-8
|View full text |Cite
|
Sign up to set email alerts
|

Stability and performance of feedback control systems with time delays

Abstract: Abstract-This paper investigates the time delay effects on the stability and performance of active feed back control systems for engineering structures. A computer algorithm is developed for stability analy sis of a SDOF system with unequal delay time pair in the velocity and displacement feedback loops. It is found that there may exist multiple stable regions in the plane of the time delay pair, which contain time delays greater than the maximum allowable values obtained by previous studies. The size, shape a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Yang and Wu [3] and Stepan [4] have studied structural systems with time delay. A study on stability and performance of feedback controls with multiple time delays is reported in [5] by considering the roots of the closed loop characteristic equation. For deterministic delayed linear systems a survey of recent methods for stability analysis is presented in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Wu [3] and Stepan [4] have studied structural systems with time delay. A study on stability and performance of feedback controls with multiple time delays is reported in [5] by considering the roots of the closed loop characteristic equation. For deterministic delayed linear systems a survey of recent methods for stability analysis is presented in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Wu [4] and Stepan [5] have studied structural systems with time delay. A study on stability and performance of feedback controls with multiple time delays is reported in [6] by considering the roots of the closed-loop characteristic equation. A method using Chebyshev polynomials to approximate general nonlinear functions of time has been developed to handle linear and nonlinear time-delayed dynamical systems with periodic coefficients [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The first challenge, documented extensively in the realm of engineering control theory, is that feedback delays destabilize output and result in oscillations and a degradation in performance (Kawato and Gomi 1992; Wolpert and Miall 1996; Ali et al 1998). One effective means of avoiding motor instability is to limit the impact of sensory feedback on motor output through reduced feedback gain (Stein and Oğuztöreli 1976).…”
Section: Problems Created By Delays In Sensory Feedbackmentioning
confidence: 99%